2022
DOI: 10.3889/oamjms.2022.8816
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of T-Scan III Digital Electronic System in Fixed Restorations Occlusal Analysis – A Review

Abstract: BACKGROUND: Occlusion is one of the most important aspects of dentistry. Dental occlusion differs among individuals. Subsequently, realizing the correct physiological occlusion is essential for the complex functioning of the stomatognathic system during the mouth prosthodontics rehabilitation. AIM: The purpose of this review paper is to provide an overview of the T-Scan system over its utility in fixed restorations occlusal analysis. MATERIALS AND METHODS: An electronic search was performed through PubMed, MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Data about the location and relative force of tooth contact are sent to the operator by the force analysis mode, which can be selected later. Two further modes are available within force analysis: Sequential, which records the intensity of interactions during mandibular movement, and instantaneous, which records mandibular locations [1,6,7] .…”
Section: Methods For Taking Occlusal Readingmentioning
confidence: 99%
“…Data about the location and relative force of tooth contact are sent to the operator by the force analysis mode, which can be selected later. Two further modes are available within force analysis: Sequential, which records the intensity of interactions during mandibular movement, and instantaneous, which records mandibular locations [1,6,7] .…”
Section: Methods For Taking Occlusal Readingmentioning
confidence: 99%
“…Сучасний рівень комп'ютерних технологій у медичній галузі відкриває можливості для глибшого розуміння особливостей функціонування зубощелепного апарату у пацієнтів. Успішність корекції оклюзійних взаємовідносин відстежують за допомогою сучасної системи T-Scan III або внутрішньоротового сканера Sirona Primescan [19,20]. Представлена система забезпечує цифровий аналіз оклюзії в режимі реального часу, як у статичному, так і в динамічному режимах, а та-кож фіксує розподіл оклюзійних сил у зубних дугах в умовах різних клінічних ситуацій.…”
Section: основна частинаunclassified
“…These occlusal analysers can be broadly classified as gauges, both quantitative and qualitative. 19 Halili R et al, 20 conducted an electronic search using Google Scholar, PubMed, MEDLINE, and Web of Science. A number of studies revealed that the T-Scan computerised occlusal analysis be able to afford measureable occlusal load and timing statistics that will allow for better protection of brittle dental ceramic and, most importantly, an improvement in the comfort and function of the patient's bite.…”
Section: In Restorative Dentistry and Prosthodonticsmentioning
confidence: 99%